Developing a learning outcome-based question examination paper tool for Universiti Putra Malaysia - Hassan, Sa'adah; Admodisastro, Novia Indriaty; Kamaruddin, Azrina; Baharom, Salmi; Che Pa, Noraini (Canadian Center of Science and Education, 2016)
Much attention is now given on producing quality graduates. Therefore, outcome-based education (OBE) in teaching and learning is now being implemented in Malaysia at all levels of education especially at higher education institutions. For implementing OBE, the design of curriculum and courses should be based on specified outcomes. Thus, the challenge for the assessment is that it should be capable of measuring whether intended outcomes have been achieved or not. Likely, by assisting lecturer in preparing examination paper that aligns with the specified outcomes is something that can help to ensure the implementation of OBE. Hence, this paper describes the development of a tool for generating question examination paper based on learning outcomes, called Learning Outcome-based Question Examination paper Tool (LoQET). LoQET is proposed for assisting lecturer in Universiti Putra Malaysia for preparing examination paper based on programme outcomes and learning outcomes set in the teaching plan and assessment entries.